Jaime Abad Vásquez, David Achig Balarezo, José Carrera Vicuña, et al., Historia de la Facultad de Ciencias Médicas de la Universidad de Cuenca, 1867-2017. Cuenca: Facultad de Ciencias Médicas de la U. de Cuenca, 2017, 164 pp. - Villarreal Rivera, Milagros (Procesos. Revista Ecuatoriana de Historia, 2018)
s. r.